STUDY ON THE APPLICATION OF FLY ASH IN ROAD AND AIRPORT CONSTRUCTION - Stepanchuk, Oleksandr Vasylovych; Shilin, Yang; Hrabovchak, Valentyna Valentynivna (Theory and practice of design, 2024)
Abstract. This thesis investigates the use of fly ash obtained from various thermal power plants in China to produce heavy concrete, especially in road and airfield construction. It includes a comprehensive analysis of fly ash samples’ chemical and physical properties, their radionuclide content, and their interaction with other materials in the concrete mixture. The study examines how fly ash affects concrete properties such as compatibility, density, frost, and water resistance. Various tests and analyses are presented, including micrographs of fly ash samples, their chemical composition, and physical and mechanical properties. The study also investigated the reaction mechanism of fly ash in hardened concrete and its role in improving the strength and durability of concrete. The conclusions emphasize the beneficial role of fly ash in concrete mixtures, especially in enhancing stability and corrosion resistance. Purpose. This study aims to analyze the effect of fly ash on various properties of concrete, such as ease, strength, and durability. It seeks to understand the chemical and physical interactions of fly ash in concrete mixtures, emphasizing improving the overall performance and sustainability of concrete by incorporating fly ash. Methodology. The study utilized modern theoretical, experimental, and physic-chemical research methods (electron microscopy). Experimental studies were conducted under laboratory conditions and on natural objects using modern measuring equipment. Results. The following two results were obtained in this study through theoretical analysis and experimental studies: 1. Incorporation of fly ash into concrete mixtures significantly improves the performance of the concrete, with the main findings including enhanced strength and durability, improved workability, and better resistance to environmental factors such as frost and water; and 2. Fly ash positively affects the physical and mechanical properties of the concrete, making it a functional additive in the production of heavy-duty concrete. Scientific novelty. The scientific novelty of this study can be summarized as follows: 1. It is the first comprehensive study of the use of fly ash from several thermal power plants in China to produce heavy-duty concrete. 2. It further deepens the understanding of the chemical and physical properties of fly ash and its effect on the performance of concrete. 3. This study provides the first detailed description of the reaction mechanism of fly ash in concrete hardening and further deepens the knowledge of utilizing industrial by-products to improve the strength and durability of concrete. Practical relevance. The practicality of this research lies in its potential to enhance the construction industry through the sustainable and efficient utilization of fly ash in concrete production. This research supports environmentally friendly construction practices by demonstrating that fly ash can be efficiently utilized in concrete mixtures. It encourages the recycling of industrial by-products, reducing waste and contributing to more sustainable construction methods.